2019
DOI: 10.1007/s40268-019-0264-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Extended In-Use Stability of the Infliximab Biosimilar PF-06438179/GP1111 Following Preparation for Intravenous Infusion

Abstract: Objective PF-06438179/GP1111 (PF-SZ-IFX) is an infliximab biosimilar. We evaluated the extended in-use physicochemical and biological stability of PF-SZ-IFX upon preparation for intravenous infusion. Methods Two batches of PF-SZ-IFX were reconstituted to a concentration of 10 mg/mL and subsequently diluted to 0.4 and 4.0 mg/mL, representing the clinically relevant range for intravenous infusion. Dilution was performed in polyethylene saline infusion bags, which are comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, in 1 mM KCl, the pH of the medium (pH ≈ 7) was lower than the pI of the most acidic species of INF (pI ≈ 7.3). Therefore, all the species of INF had a net positive charge under those conditions [ 40 ], so the decrease in ζ potential in the INF-loaded formulations could not be attributed to a direct effect of the presence of a significant amount of surface-adsorbed infliximab.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in 1 mM KCl, the pH of the medium (pH ≈ 7) was lower than the pI of the most acidic species of INF (pI ≈ 7.3). Therefore, all the species of INF had a net positive charge under those conditions [ 40 ], so the decrease in ζ potential in the INF-loaded formulations could not be attributed to a direct effect of the presence of a significant amount of surface-adsorbed infliximab.…”
Section: Resultsmentioning
confidence: 99%
“…Stability studies have demonstrated that monoclonal antibodies have long-term stability allowing preparation in advance. Infusions of pembrolizumab are stable for 7 days, infliximab and bevacizumab until 45 days, nivolumab for 28 days [41][42][43][44][45][46][47]. Rituximab and trastuzumab infusion are stable for 6 months when stored between 2 and 8 °C [48,49].…”
Section: Photodegradation Of Chloramphenicolmentioning
confidence: 99%